2004
DOI: 10.1002/app.20560
|View full text |Cite
|
Sign up to set email alerts
|

Swelling behavior of polyelectrolyte complex hydrogels composed of chitosan and hyaluronic acid

Abstract: Polyelectrolyte complex (PEC) hydrogels composed of various weight ratios of chitosan and hyaluronic acid were prepared. The PEC hydrogels were formed by the reaction of the oppositely charged chitosan polymers. The PEC films swelled in water rapidly, reaching equilibrium within 30 min, and exhibited relatively high swelling ratios, 243-322%, at 25°C. The swelling ratio increased with increasing temperature. The transport phenomena of all PEC samples were non-Fickian and diffusion and relaxation controlled. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
(14 reference statements)
3
14
0
4
Order By: Relevance
“…These results suggest that in the first scaffold the mechanism of water transport is controlled by a Fickian diffusion process, while in the PEC scaffold the rate of water transport responds to a non-Fickian diffusion process, which depends of diffusion and of the macromolecular chain relaxation. Our results are in good agreement with those presented by Kim et al [47] for chitosan-hyaluronic acid polyelectrolyte complexes and by Giers zewska-Dru _ zyń ska et al [48] for chitosan-alginate membranes.…”
Section: Scaffold Stability and Swelling Behaviorsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that in the first scaffold the mechanism of water transport is controlled by a Fickian diffusion process, while in the PEC scaffold the rate of water transport responds to a non-Fickian diffusion process, which depends of diffusion and of the macromolecular chain relaxation. Our results are in good agreement with those presented by Kim et al [47] for chitosan-hyaluronic acid polyelectrolyte complexes and by Giers zewska-Dru _ zyń ska et al [48] for chitosan-alginate membranes.…”
Section: Scaffold Stability and Swelling Behaviorsupporting
confidence: 93%
“…The hydrogel swelling mechanism can be interpreted through the two processes, concentration gradient-controlled diffusion and relaxation-controlled swelling; both of them contribute to the rate and extent of penetrant sorption into the polymer [47]. As previously mentioned, to determine the n exponent the kinetics of such process could be analyzed through the Fick model (Eq.…”
Section: Scaffold Stability and Swelling Behaviormentioning
confidence: 99%
“…65 QCM study of alginate/chitosan coatings on gold coated quartz crystals showed adsorption of various amounts of water depending on environmental humidity. Saturated humidified air caused a decrease of the frequency, whereas the frequency signal was stable in a dry air environment.…”
Section: Resultsmentioning
confidence: 99%
“…The rate and extent of penetrant sorption into the polymer are determined by both concentration gradient-controlled and/or relaxation-controlled diffusion [55,56]. The diffusion categories of molecules into polymers when the maximum swelling degree is less or equal to 60 wt% are deducted from the exponent, n , of the following expression (Equation 4) [5759] …”
Section: Resultsmentioning
confidence: 99%